Karakteristik Film Komposit PVA-Pulp Putih Akasia Terfibrilasi (Characteristics of the Composite Film of PVA-Fibrillated Acacia Bleached Pulp) - Firda A Syamani; Wida B Kusumaningrum (Masyarakat Peneliti Kayu Indonesia, 2013)
In the present experiments, the fibrillated bleached pulp of acacia (Acacia mangium) was used as reinforcing filler in the poly vinyl alcohol (PVA) matrix resin. Fibrillation processes of the pulp involved the use of disc refiner, ultraturrax (UT) and ultrasonicator (US). The composite film of PVA and 1% fibrillated pulp was prepared through film casting method. The morphology of fibrillated pulp was observed under SEM and the tensile properties (i.e. tensile strength, elongation at break and Young’s modulus) of the composites were determined by the use of universal testing machine (UTM). It was found that 30 cycles disc refining of the pulp proceeded with 10 min US treatment resulted in a fiber diameter of approximately 8.35 μm. PVA and fibrillated bleached pulp composites was transparent with thickness and density of 0.07-0.19 and 1.1-1.3 g cm-3, respectively. The Young’s modulus of the composites with 30 cycles disk refining of the pulp was much higher (122.7 Nm m-2) compared to that of pure PVA film (66.4 Nm m-2). The tensile strength of PVA and fibrillated bleached pulp composites and pure PVA was unchanged. Key words: Acacia mangium, film casting, mechanical fibrillation, mechanical properties, morphology